Financial Times Handbook of Corporate Finance, 2nd Edition - Arnold, Glen (Pearson Business, 2010)
The Financial Times Handbook of Corporate Finance is the authoritative introduction to the principles and practices of corporate finance and the financial markets. Whether you are an experienced manager or finance officer, or youu0092re new to financial decision making, this handbook identifies all those things that you really need to know: · An explanation of value-based management · Mergers and the problem of merger failures · Investment appraisal techniques · How to enhance shareholder value · How the finance and money markets really work · Controlling foreign exchange rate losses · How to value a company The second edition of this bestselling companion to finance has been thoroughly updated to ensure that your decisions continue to be informed by sound business principles. New sections include corporate governance, the impact of taxation on investment strategies, using excess return as a new value metric, up-to-date statistics which reflect the latest returns on shares, bonds and merger activities and a jargon-busting glossary to help you understand words, phrases and concepts. Corporate finance touches every aspect of your business, from deciding which capital expenditure projects are worth backing, through to the immediate and daily challenge of share holder value, raising finance or managing risk. The Financial Times Handbook of Corporate Finance will help you and your business back the right choices, make the right decisions and deliver improved financial performance. It covers the following areas: · Evaluating your firmu0092s objectives · Assessment techniques for investment · Traditional finance appraisal techniques · Investment decision-making in companies · Shareholder value · Value through strategy · The cost of capital · Mergers: failures and success · Merger processes · How to value companies · Pay outs to shareholders · Debt finance · Raising equity capital · Managing risk · Options · Futures, forwards and swaps · Exchange rate risk.